The Effect Of Children Education On Economic Growth In Aceh Province-Indonesia - Hermanto Joesoef (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study aims to analyze the effect of children education on economic growth in the Aceh Province. The variables included the rate of literacy, school enrolment, the highest level of education attainment and the education expenditure. The data analyzed in the form of panel data which is a combination of time series data and cross section data. The data is sourced from the Statistic Agency, Ministry of Finance, Ministry of National Education and other relevant sources. Data analysis was performed quantitatively with Fixed Effect Model utilizing multiple regression equation with the period of the observation of 2010-2020.The results showed that the literacy rate does not affect significantly to economic growth, whereas the other three variables: education enrollment rates, highest level of education and the education budget affect economic growth in Aceh Province.